Слово джентльмена: роман / Сюзанна Энок ; перевод с английского В. А. Сазанова - Энок Сюзанна (Шарм, 2005)
Экземпляры: ф.6 (20171219) / Инвентарный номер: 2104 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Э 66 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44